1998
DOI: 10.1002/(sici)1521-4141(199811)28:11<3763::aid-immu3763>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T cell responses in mice lacking MHC class II molecules specifically on B cells

Abstract: The role of B lymphocytes in initiating and maintaining a CD4+ T cell response has been examined using a variety of strategies, but remains controversial because of weaknesses inherent to each of the approaches. Here, we address this issue by measuring CD4+ T cell priming both in mutant mice devoid of B cells and in chimeric animals lacking major histocompatibility complex class II molecules specifically on B cells. We find that peptide and some protein antigens do not require B cells expressing class II molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 53 publications
1
19
0
1
Order By: Relevance
“…Thus, B cells may contribute to the full expansion of Ag-specific CD4 T cells to drive Th2 differentiation, but whether this requires Ag presentation is controversial (12)(13)(14). However, the effects of B cell Ag presentation on Th1 CD4 ϩ differentiation are unknown.…”
Section: T Cells In the Thymus And Function To Present Peptide Ags Tosupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, B cells may contribute to the full expansion of Ag-specific CD4 T cells to drive Th2 differentiation, but whether this requires Ag presentation is controversial (12)(13)(14). However, the effects of B cell Ag presentation on Th1 CD4 ϩ differentiation are unknown.…”
Section: T Cells In the Thymus And Function To Present Peptide Ags Tosupporting
confidence: 91%
“…Because isotype switching requires cognate interactions between activated CD4 T cells and Ag-specific B cells (14,45), the level of anti-OVA IgG in the serum 13 days after immunization was measured. As expected, no OVA-specific IgG was detected in the absence of cognate Ag or MHCII, whereas wild-type I-A ␤ b ϩ/Ϫ mice immunized with OVA protein and LPS had elevated titers of specific Abs.…”
Section: In Vivo Presentation Of Protein Agsmentioning
confidence: 99%
“…However, B cells can influence T cell function through a variety of means (21,(34)(35)(36)(37)(38). It has been suggested that they are involved in regulating the activation status and number of effector T lymphocytes based on observations of abnormal CD4 ϩ T cell responses in B cell-deficient mice (36, 37).…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that germinal center formation involves quantitatively (or qualitatively) more stringent T cell-B cell interactions than the interactions resulting in Ig subclass switching. It is unlikely that the IgG production in these mice reflects bystander activation of B cells as a result of T cell priming by dendritic cells, since IgG production after OVA immunization requires Ag presentation by the B cells themselves (35) The Ab response after immunization prompted us to analyze Ag presentation in more detail. Different epitopes from a single Ag may display different DM requirements (14,28), and it was possible that one or several epitopes were still presented relatively efficiently by DM-deficient APCs.…”
Section: Discussionmentioning
confidence: 99%